Hovedstadens shantytowns? Lysthuse i hovedstadens første forstadsdannelse - Bro, Henning (Arbejderhistorie, 2026)
Not only the Copenhagen neighborhoods, but also the suburbanization outside reflected the extreme class diﬀerences in society in the first decades of the 20th century. From monstrous magnificent villas and fashionable apartments in the apartment buildings in the Gentofte suburbs to primitive small houses in the other suburbs that, without any kind of development, simultaneously grew up on speculatively mass-divided areas in the northwest and west regions. Since a significant part of the small houses were built as summer cottages with the reuse of wooden packing crates and old building parts and were also illegally inhabited all year round, subsequent research literature has referred to the suburbs in the northwest and west regions as shanty towns, the Wild West or Klondyke. This article focuses on the background, character and development of these summer cottages, but argues that the aforementioned highly value-laden designations for the northwest and west suburbs are somewhat overexposed. The summer cottages constituted a smaller and otherwise varying proportion of the total number of small houses in these suburbs and were also built on the developer’s own land and not on annexed third-party property. In addition, the government legalized the unlawful year-round occupancy of the summer cottages, as they helped relieve the pressure of the housing shortage in Copenhagen, which up to, during and long after the First world war had led to large expenditures for government loans and subsidies for municipal and other social housing construction with small and medium-sized apartments, which came to form the foundation of the housing policy of the early welfare state. Finally, during the 1920s and 1930s, the summer cottages were replaced by small houses with foundation walls or expanded, developed and modernized so that they were suitable for year-round occupancy. If the summer cottages and the year-round residence of these were a relatively short-lived phenomenon, the article shows that, together with the lack of construction maturity and the large influx of workers and low-level employees, they posed significant challenges to the local suburban municipalities. However, these were overcome relatively quickly in the early social democratically governed suburban municipalities of Gladsaxe and tårnby. In the form of municipal road construction, sewage systems, pressurized water supply schemes, institutions that corresponded to suburban development, and schemes that promoted the construction of small houses with foundation walls instead of summer cottages. These suburbs thus developed more quickly into welfare suburbs than the suburbs in Hvidovre and Rødovre. Here, the bourgeois-controlled municipalities had blocked similar measures as in Gladsaxe and Tårnby. with the result that the social democratic majorities that were achieved in Hvidovre and Rødovre during the 1920s had to establish the very basic framework for suburban development with delay. Hvidovre and Rødovre thus only really moved up into the category of welfare suburbs in the late 1940s.